Penerapan Pendekatan Keterampilan Proses Sains dalam Model Pembelajaran Guided Discovery untuk Meningkatkan Hasil Belajar IPA Fisika Pada Siswa Kelas VIIa SMPN 8 Mataram Tahun Ajaran 2015/2016 - Enol Azizirrahim; Sutrio Sutrio; Gunawan Gunawan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
The purposes of this research is to improve learning outcomes of students at SMPN 8 Mataram. This is a classroom action research with two cycles. Each cycles include planning, implementation, observation, evaluation and reflection. Implementation of guided discovery learning model made 5 phases: introduction, orientation of students on the issue, conducting, presenting and evaluating results. In the first cycle, obtained an average student learning outcomes at 74.82, while in the second cycle of 81.75. Classical mastery learning in the first cycle of 64.7% and in the second cycle of 86%. Activities of students and teachers that are in the active category. Based on these results it can be concluded that the application of guided discovery learning models with science process skills approach is proven to increase physics learning outcomes of students at SMPN 8 Mataram.